Gut microbiota profiling of Apis cerana indica across biodiversity hotspots in the Western Ghats, India - Jenifer Sheeba Joseph; Selva Babu Selvamani; Venkatesan Thiruvengadam; Gandhi Gracy Ramasamy; Sabtharishi Subramanian; Gopalakrishnan Menon; G. Sivakumar; C. Manjunath (Molecular Biology Reports, 2026)

Process-dependent removal of fine microplastics in pilot- and full-scale sewage treatment plants - Shaima Iskandarani; Sarvajith Manjunath; Xiaowen Zhu; Yaping Zhang; Rosa Busquets; Pascal E. Saikaly; Luiza C. Campos (Journal of Water Process Engineering, 2026)

Cis-regulatory divergence and misexpression of spermatogenesis genes underlie hybrid male sterility in the Drosophila bipectinata species complex - M. Manjunath; C. S. Damini; V. Shakunthala (Genetica, 2026)

Zinc oxide assisted photocatalytic degradation of mixed effluents of rhodamine B dye and paracetamol drug mediated by acid blue 25 dye - C. Shalinibabu; Manjunath Pattar; K.K. Nagaraja; S. Pramodini (Journal of Water Process Engineering, 2026)

Phenotypic characterization of Mangalore melon (Cucumis melo subsp. agrestis var. acidulus) accessions from Southern India based on qualitative and quantitative traits - Ratnakar Manjunath Shet; Raghavendra Gunnaiah; Shantappa Tirkannanavar; Shivanand Hongal; Virupakshi Hiremata; K. C. Venugopal (Genetic Resources and Crop Evolution, 2025)

Infraspecific hybridisation of muskmelon (Cucumis melo ssp. melo) with mangalore melon (C. melo ssp agrestis var. acidulus) for extended shelf life and improved yield - K. C. Venugopal; Ratnakar Manjunath Shet; Raghavendra Gunnaiah; Rekha B. Chittapur; Virupakshi Hiremata; Shashikanth Evoor; Sarvamangala Cholin; Guranna Prabhuling (Genetic Resources and Crop Evolution, 2025)

Deciphering salt stress response of pomegranate genotypes (Punicagranatum L.): a comprehensive evaluation - Chandrakant Awachare; Janhavi Pravin Patel; Sebin Sara Solomon; Pinky Raigond; K. Dhinesh Babu; Shilpa Parashuram; Susheel Kumar Sarkar; Mahesh Kumar; C. T. Manjunath Prasad; Rajiv Arvind Marathe; Nripendra Vikram Singh (Plant Physiology Reports, 2025)

Spectroscopic Studies of Red Emitting ZrO2:Eu3+ Nanophosphors using Judd−Ofelt Theory for Lighting Applications - H. C. Madhusudhana; C. Manjunath (Journal of Fluorescence, 2025)

Estimation of Monsoon Seasonal Precipitation Teleconnection with El Niño-Southern Oscillation Sea Surface Temperature Indices over the Western Ghats of Karnataka - Vinay Doranalu Chandrashekar; Amba Shetty; Manjunath Patel G C (Asia-Pacific Journal of Atmospheric Sciences, 2024)

A comprehensive review on the effect of turbulence promoters on heat transfer augmentation of solar air heater and the evaluation of thermo-hydraulic performance using metaheuristic optimization algorithms - G. K. Pramod; U. C. Arunachala; N. Madhwesh; M. S. Manjunath (Environment, Development and Sustainability, 2024)
Solar air heaters are characterized by poor thermal performance due to limited heat transfer capability of air, thereby necessitating the need for design modifications. Among a different system performance augmentation technique, turbulence promotors are widely used owing to its effectiveness. Based on design parameters such as geometry, size, pitch and arrangement of turbulence promoters, varying levels of heat transfer increment with the pressure drop penalty is achievable. This led to the development of new designs which could offer on optimum thermo-hydraulic performance for a wide range of Reynolds number. Such research invariably requires a thorough insight of data related to various design parameters and optimal thermal–hydraulic performance range. This article provides a detailed overview of various turbulence promotor designs and their optimal thermal–hydraulic performance ranges compiled from a wide spectrum of experimental and numerical studies. Apart from outlining the general flow characteristics of each turbulator design, this study also evaluates different metaheuristic optimization algorithm such as bonobo optimization (BO), particle swarm optimization and teaching–learning-based optimization algorithm for enhancing the thermal–hydraulic performance parameter (THPP). The study shows that the BO algorithm does not exhibit local trapping due to its self-adapting nature of the optimized parameters which makes it a promising choice for THPP optimization studies in air heater applications. The extensive review also shows that the arrangement pattern of rib turbulator plays a key role in thermo-hydraulic performance augmentation. Based on the BO optimization analysis, the range of THPP is determined for the optimized geometry of turbulence promoters. In the pool of rib design, transverse prism rib, multi-V-rib, multi-V-shaped rib with staggered rib, sinewave-shaped rib with gap and S-shaped ribs exhibits an optimal THPP range of 2.05–3.32, 2.43–2.94, 3.00–3.61, 1.58–3.40 and 2.05–3.74, respectively. Other turbulence promotor designs such as winglet vortex generator, dimple protrusion in arc shape and multi-V-baffles exhibits optimal THPP range of 1.95–2.2, 2.44–3.68 and 1.75–2.01, respectively. At the end, the study proposes key research gaps such as the use of combined ribs and vortex generators and discrete fin arrays of different geometry as future scope of research. Graphical abstract

Effects of fiber addition on performance of high-performance alkali activated slag concrete mixes: An experimental evaluation - R. Manjunath; Mattur C. Narasimhan; Shivam Kumar (European Journal of Environmental and Civil Engineering, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Cellular Thermometry Considerations for Probing Biochemical Pathways - Manjunath C. Rajagopal; Sanjiv Sinha (Cell Biochemistry and Biophysics, 2021)

First occurrence of Diaphorina citri in East Africa, characterization of the Ca. Liberibacter species causing huanglongbing (HLB) in Tanzania, and potential further spread of D. citri and HLB in Africa and Europe - Mpoki M. Shimwela; Hossein A. Narouei-Khandan; Susan E. Halbert; Manjunath L. Keremane; Gerald V. Minsavage; Sujan Timilsina; Deogracious Protas Massawe; Jeffrey B. Jones; Ariena H. C. van Bruggen (European Journal of Plant Pathology, 2016)

Host genetic variations in glutathione-S-transferases, superoxide dismutases and catalase genes influence susceptibility to malaria infection in an Indian population - Rayzel C. Fernandes; Marriyah Hasan; Himanshu Gupta; K. Geetha; Padmalatha S. Rai; Manjunath H. Hande; Sydney C. D’Souza; Prabha Adhikari; Angela Brand; Kapaettu Satyamoorthy (Molecular Genetics and Genomics, 2015)

Study of morpho-physiological, phenological and reproductive behaviour in protogynous lines of Indian mustard [Brassica juncea (L.)] - U. S. Chandrashekar; Malavika Dadlani; K. Vishwanath; S. K. Chakrabarty; C. T. Manjunath Prasad (Euphytica, 2013)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Risk prediction—Homocysteine in Coronary Heart Disease - Rao B Harish; V. Govindaraju; C. N. Manjunath (Indian Journal of Clinical Biochemistry, 2007)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

Hyperhomocysteinemia: An emerging risk factor for cardiovascular disease - V. Govindaraju; Neelam; C. N. Manjunath; H. Venkataramiah; T. R. Raghu (Indian Journal of Clinical Biochemistry, 2003)

Genomic structure, cDNA mapping, and chromosomal localization of the mouse homeobox gene, Hex - Bidyut Ghosh; Harris C. Jacobs; Leanne M. Wiedemann; Anthony Brown; Fiona K. Bedford; Manjunath A. Nimmakayalu; David C. Ward; Clifford W. Bogue (Mammalian Genome, 1999)